Evaluation of Aryoseven Safety (Recombinant Activated Factor VII) in Patients with Bleeding Disorders (An Observational Post-Marketing Surveillance Study) - Gholamreza Toogeh; Hassan Abolghasemi; Peyman Eshghi; Mohammadreza Managhchi; Mohammadreza Shaverdi-niasari; Katayoon Karimi; Samin Roostaei; Neda Emran; Alireza Abdollahi (Iranian Society of Pathology, 2016)
Background: Recombinant activated factor VII induces hemostasis in patients with coagulopathy disorders. AryoSeven™ as a safe Iranian Recombinant activated factor VII has been available on our market. This study was performed to establish the safety of AryoSeven on patients with coagulopathy disorder. Methods: This single-center, descriptive, cross sectional study was carried out in Thrombus and Homeostasis Research Center ValiAsr Hospital during 2013-2014. Fifty one patients with bleeding disorders who received at least one dose of Aryoseven were enrolled. Patients' demographic data and adverse effect of drug and reaction related to Aryoseven or previous usage of Recombinant activated FVII were recorded in questionnaires. Finally data were analyzed to compare side effects of Aryoseven and other Recombinant activated FVII brands. Results: Aryoseven was prescribed for 51 Patients. Of all participants with mean age 57.18+21.38 yr, 31 cases were male and 26 subjects had past history of recombinant activated FVII usage. Glanzman was the most frequent disorder followed by congenital FVII deficiency, hemophilia with inhibitors, factor 5 deficiency, acquired hemophilia, hemophilia A with inhibitor, and hemophilia A or B with inhibitor. The majority of bleeding episodes had occurred in joints. Three patients (5.9%) complained about adverse effects of Aryoseven vs. 11.5 % about adverse effects of other brands. However this difference was not significant, statistically. Conclusion: Based on monitor patients closely for any adverse events, we concluded that Aryoseven administration under careful weighing of benefit versus potential harm may comparable with other counterpart drugs.   How to cite this article: Toogeh G, Abolghasemi H, Eshghi P, Managhchi M, Shaverdi-niasari M, Karimi K, et al. Evaluation of Aryoseven Safety (recombinant activated factor VII) in patients with bleeding disorders (An observational post-marketing surveillance, study). Iran J Pathol. 2016; 11(3):204-9.